PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PASIEN RAWAT INAP DI SMC RUMAH SAKIT TELOGOREJO - Hendy Winardi; Wahyu Hidayat; Andi Wijayanto (Universitas Diponegoro, 2014)
A good service quality always connected with the customer satisfaction. SERVQUAL method to measure the service quality of SMC Telogorejo Hospital shows that one of the service quality's variable will be outstanding among the others. The purpose of this research is to determine the influence of service quality on inpatient of SMC Telogorejo Hospital's costumer satisfaction. The type of this research is associative research with data collection techniques by interviewing using questionnaire. Analysis of data using simple linear regression and multiple regression test with SPSS 16.0. While the hypothesis testing using t test, f test, correlation coefficient and the coefficient of determination. The result showed that service quality have an influence on customer satisfaction with a correlation coefficient of 0,899 and coefficient of determination of 80,7%. The most determining variable of service quality, which influenced the customer satisfaction, is empathy with a correlation coefficient of 0,831 and coefficient of determination of 69%. Together, the five dimension of service quality have influence on customer satisfaction with the equation Y = 0,732 + 0,043X1 + 0,253X2 + 0,280X3 + 0,457X4 + 0,502X5. This means with a better from each dimension of service quality, the customer satisfaction will be higher. The conclusion of this research are service quality have an influence on job satisfaction and the most determined variable of dimension of service quality is empathy. Suggestion for the company, they should mainting the good performance of service quality with continous evaluation and maintaining the service excellent to reach the international standart hospital.